A Prototype of Job Distribution System for Community: A case study of a Corporate Social Responsibility using NFC - Lamphun, Pornlapas Na; Lamphun, Phannachet Na (INTERNATIONAL SCIENTIFIC JOURNAL OF ENGINEERING AND TECHNOLOGY (ISJET), 2019)
Corporate Social Responsibility (CSR) is one of the activities that help make society better. One of CSR’s activities is to create jobs to support communities. To operate such activity, can be time and resource consuming for the organization. Also it might be hard for people to join due to different personal restrictions. A prototype of this Job Distribution System for Community was implemented to help increase income for people in community. The application has been tested in one organization with three communities. The result showed that the prototype application can help manage CSR project and help people in the community to be able to find jobs that suit their preferences.